An in vitro study exploring the role of mucin in the protein-flavor binding mechanism - Cristina Barallat-Pérez; Emma Khazzam; Hans-Gerd Janssen; Sara Martins; Vincenzo Fogliano; Teresa Oliviero (npj Science of Food)
Abstract In the mouth, food flavors interact with salivary proteins like mucin, which protects mucosal surfaces and influences the rate of aroma release. The role of mucin in the protein-flavor binding mechanism was evaluated in a model system in vitro using GC-MS. The number of binding sites (n) and binding constants (K) of commercial food protein isolates (PIs) and carbonyl compounds were calculated using Klotz plots. Results suggested a linear relationship between PIs and carbonyl compounds, where K increased with the flavor chain length, and n ranged from n = 0.021 to 7.194. Mucin addition to flavor-protein systems increased flavor binding up to fifteen times. At 0.01(w/v)% mucin, structural changes enhanced flavor binding. At higher mucin levels, further unfolding leads to aggregation, restricting access of the flavor molecules to the binding sites. These results confirmed the role of flavor structural characteristics and mucin on flavor binding, essential for optimal food design.